2021
DOI: 10.1177/0306624x211027487
|View full text |Cite
|
Sign up to set email alerts
|

Self-Control, Risky Lifestyles, and Victimization among Chinese Adolescents

Abstract: Violent and property victimization among Chinese adolescents remains a social problem, yet studies that incorporate individual characteristics and situational/contextual factors to explain such victimization remain scarce. Drawing upon survey data collected from a large, representative sample of middle school students from two areas in Guizhou Province, China, we test Schreck’s integrated model of victimization, finding that self-control has both direct and indirect influences on violent and property victimiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 60 publications
1
3
0
Order By: Relevance
“…Results also indicate support for the risky lifestyles perspective wherein Korean adolescents who engaged in bullying perpetration and peer delinquency were more likely to belong to the early-onset decreasing class. This result confirms findings in an extensive body of scholarship that risky lifestyles are a cause of victimization and bullying perpetration, including interacting/hanging out with delinquent peers (Cho, 2017(Cho, , 2019Qu et al, 2022;Schreck et al, 2004;Stogner et al, 2014) and participating in delinquent behavior (Cho, 2017(Cho, , 2019Cho & Wooldredge, 2018;Savolainen et al, 2009). Involvement in these activities predisposes youth to victimization.…”
Section: Discussionsupporting
confidence: 87%
“…Results also indicate support for the risky lifestyles perspective wherein Korean adolescents who engaged in bullying perpetration and peer delinquency were more likely to belong to the early-onset decreasing class. This result confirms findings in an extensive body of scholarship that risky lifestyles are a cause of victimization and bullying perpetration, including interacting/hanging out with delinquent peers (Cho, 2017(Cho, , 2019Qu et al, 2022;Schreck et al, 2004;Stogner et al, 2014) and participating in delinquent behavior (Cho, 2017(Cho, , 2019Cho & Wooldredge, 2018;Savolainen et al, 2009). Involvement in these activities predisposes youth to victimization.…”
Section: Discussionsupporting
confidence: 87%
“…First, our study consistently showed that male students had higher lifetime prevalence of club drug use than female students [11,13,31,33]. In China, licit drugs (e.g., smoking and drinking) use was socially accepted and usually regarded as a symbol of independence and social status among males [55,56], and males might exhibit lower levels of self-control than females [57], all of which might increase the risk of illicit drugs use among males. Second, the type of associated factors had some distinction between different genders.…”
Section: Discussionmentioning
confidence: 60%
“…Despite these adverse consequences of victimization, young adolescents are the least likely group to report their victimization to police and others, making it more difficult to prevent its adverse impact in earlier stages [ 68 ]. Thus, it is essential for scholars to completely understand the etiology of adolescent victimization and life processes that place them at heightened risk of being victimized [ 76 , 77 , 78 ]. Identifying risk factors related to victimization with young adolescents can promote adolescents’ successful transition to healthy adulthood by providing practical preventive measures.…”
Section: Discussionmentioning
confidence: 99%